Ecosystem‐scale loss of grazing habitat impacted by abundance of dominant herbivores. Issue 6 (12th June 2019) - Uher‐Koch, Brian D.; Schmutz, Joel A.; Wilson, Heather M.; Anthony, R. Michael; Day, Thomas L.; Fondell, Thomas F.; Person, Brian T.; Sedinger, James S.
Abstract: Grazing lawns, patches of grazing‐tolerant plants with high nutrient value, provide important habitat for herbivores, and changes in abundance can impact herbivore populations. Grazing lawns are maintained in quality and quantity by repeated grazing and are a result of a positive feedback since the availability of grazing lawn can increase herbivore populations and increased herbivore populations can result in an increase in grazing lawn extent. We sampled aerial imagery from a long‐term dataset (>20 yr) at an internationally important breeding area for avian herbivores to model changes in grazing lawn abundance over time and identify the possible factors impacting those changes, including numbers of breeding birds, their primary predator, and spring phenology. Our data suggest that avian herbivores and their predators likely exert strong impacts on plant communities and may drive vegetation abundance. Decreases in the number of herbivore nests in our study coincided with an almost complete lack of grazing lawn in the mid‐2000s. Any factors dictating the amount of grazing lawn available for avian herbivores could strongly influence breeding success and the maximum size of these populations. Our results demonstrate the importance of studying complex interactions among predators, herbivores, and plants, and population moderation by both bottom‐up and top‐down processes.